Experimental development of fabry-perot fiber-optic metal ion sensor based on layer-by-layer (chitosan/polystyrene sulfonate) substrate and ionophore (carboxymethyl 18-crown-6). - Yu, Feng Jen. (2013)
Water pollution by heavy metal is an increasingly concerned worldwide issue, thus it is necessary to develop an effective sensor that is cost-effective, safe and sensitive. In this project, development of a novel label-free Fiber-Optic Fabry-Perot interferometry (FPI) metal ion detector based on a successful immunosensor with similar mechanism is proposed. 2 configurations of the sensor were proposed, one with an additional SMF cap and one without. Using the EDC / NHS coupling mechanism, the sensing element (ionophore) was attached to the polyelectrolyte substrate (Chitosan / Polystyrene Sulfonate) formed by performing polymeric layer-by-layer (LBL) self-assembly technique. In order to assess the feasibility of the sensor application upon metal ions, ionic potassium solution chosen to be the target to simulate heavy metal ions in water, while the chelation compound carboxymethyl 18-crown-6 (CMC) was selected as the sensing element. Unfortunately, the fabricated sensors displayed minimal response regardless the configuration. It is postulated that the chelation process of metal ions does not produce significant changes in effective optical thickness. It is recommended to experiment upon other sensing elements with different sensing mechanisms.